Effect of Seed Rate and Seed Viability on the Number of Prick Able Seedlings Of Eucalyptus grandis - Sharma. C., J. K.; Yesodharan, K. (Indian Forester, 1990)
Different seed rates (2.8, 5.6 and 7.0 gm2-1) affected significantly the seedling density as well as availability of prickable seedlings of Eucalyptus grandis from the seedbed nursery. Percentage of prickable seedlings in respect of seedling density decreased as the seed rate increased pattern of availability of number of seedlings at different time period being the same. As a part of the nursery management practices it is suggested to determine the seed rate for raising the nursery economically and ensuring healthy disease-free nursery stock.